Development of Vocabulary Teaching Materials to Improve Grammar Skills in Writing Narratives of Grade V Students of SDN 060939 Medan Amplas in 2024-2025 - Hidayat, Muhammad; Kartolo, Rahmat; Ginting, Sri Ulina Beru (Journal of English Language and Education, 2025)
The purpose of this study was to describe the ability of fifth grade students of UPT SD Negeri 060939, Medan Amplas District, in the 2024-2025 academic year to use vocabulary and describe the development of vocabulary teaching materials and the abilities of fifth grade students of UPT SD Negeri 060939, Medan Amplas District, in the 2024-2025 academic year. Using samples in class This study was conducted in class V of UPT SD Negeri 060939, Medan Amplas District, in the 2024-2025 academic year, with 60 students divided into 2 classes, namely the experimental class and the control class. By using the experimental class using the development of audio-visual teaching materials in the form of videos and the control class using the development of individual teaching materials in the form of textbooks. This study uses a 2 x 2 Anova research design using the general linear model data analysis technique on SPSS IBM 22, so the research results obtained are 1) there is an increase in the ability of grade V students of UPT SD Negeri 060939 Medan Amplas District in the 2024-2025 academic year to use vocabulary with a sig value 0.05 (0.00 0.05) and 2) there is an influence of the development of vocabulary teaching materials and the ability of grade V students of UPT SD Negeri 060939 Medan Amplas District in the 2024-2025 academic year with a sig value 0.05 (0.00 0.05). Thus, it can be concluded that the experimental class is better than the control class. The experimental class is more prepared and generates enthusiasm in writing narrative essays, so that events can be informed properly and correctly.